2020
DOI: 10.1007/s40620-020-00871-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of computed tomography-based assessment of skeletal muscle mass in hemodialysis patients

Abstract: Background: Sarcopenia is a major health issue especially in patients on maintenance hemodialysis. Low skeletal muscle mass is included in the diagnostic criteria for sarcopenia. The skeletal muscle mass is usually evaluated by modalities such as bioimpedance analysis (BIA) or dual-energy x-ray absorptiometry, however the assessment of skeletal muscle mass using computed tomography (CT) images has not been established. The purpose of the study was to investigate the feasibility of the assessment of skeletal mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
(26 reference statements)
1
17
0
Order By: Relevance
“…Kurumisawa et al 21 demonstrated that the CT-measured psoas muscle index, assessed before cardiovascular surgery, is a predictor of long-term survival after cardiac surgery. Similarly, Takata et al 22 reported that the CT-measured psoas muscle index is correlated with the bioelectrical impedance analysis–measured skeletal muscle mass index, where a low psoas muscle index is associated with an increased risk of mortality. Moreover, they suggested that the psoas muscle index assessed using CT can be an alternative to bioelectrical impedance analysis in patients undergoing hemodialysis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Kurumisawa et al 21 demonstrated that the CT-measured psoas muscle index, assessed before cardiovascular surgery, is a predictor of long-term survival after cardiac surgery. Similarly, Takata et al 22 reported that the CT-measured psoas muscle index is correlated with the bioelectrical impedance analysis–measured skeletal muscle mass index, where a low psoas muscle index is associated with an increased risk of mortality. Moreover, they suggested that the psoas muscle index assessed using CT can be an alternative to bioelectrical impedance analysis in patients undergoing hemodialysis.…”
Section: Discussionmentioning
confidence: 90%
“…Only a few studies have examined the association between CT-measured sarcopenia indices and mortality in patients undergoing hemodialysis 20 22 . Although the use of PMTH for predicting mortality remains unclear, we hypothesized that low PMTH may be an increased risk of mortality in this population.…”
Section: Introductionmentioning
confidence: 99%
“…CT-based evaluation of the psoas muscle cross-sectional area and subsequent calculation of PMI has shown good inter-rater reliability [ 16 , 22 ]. Furthermore, PMI correlated with the skeletal muscle mass in dialysis patients [ 16 , 23 ]. Therefore, annual CT scans performed to detect acquired cystic and malignant kidney disease are useful for HD patients [ 23 , 24 ] and may be utilized for the assessment of trunk muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…It is being recognized as a great health issue in the elderly population [12][13]. A growing number of evidences have revealed that sarcopenia is related to cardiovascular disease [14], cognitive function [15], physical performance [16], and mortality [17]. The pathogenesis of sarcopenia involves various conditions such as malnutrition and in ammation.…”
Section: Introductionmentioning
confidence: 99%